Peptide Vaccines for Malaria (2006)
Obtaining a highly effective malaria vaccine is a worldwide priority. The first approach aimed at obtaining a malarial vaccine using synthetic peptides was a polymeric chimeric molecule named SPf66, which conferred limited protective efficacy in Aotus monkeys and in large human field-trials. Our efforts then became focused on obtaining a second generation malarial vaccine based on the rational selection of conserved high activity binding peptides (HABPs) whose critical binding residues were to be systematically replaced by others precisely selected. An alternative approach has consisted of replacing peptide bonds involving these HABPs’ critical binding residues; this has also returned promising results to date. Our overall results have suggested a correlation between modified HABPs’ three-dimensional structure, HLA-DR ?1* binding preferences, and their protection-inducing capacity in monkeys. Basic knowledge of a parasite's functionally active peptides, their 3D structure, and their interaction for forming the MHC II-peptide-TCR complex will thus contribute toward designing fully effective multicomponent, multistage, subunit-based malarial vaccines.